Orchids, intersex and the auto/biographical project - Hart, Phoebe (Studies in Documentary Film, 2013)
Auto/biographical documentaries ask audiences to take a ‘leap of faith’, not being able to offer any real 'proof of the people and events they claim to document, other than that of the film-maker's saying this is what happened. With only memory and history seen through the distorting lens of time, ‘the authenticity of experience functions as a receding horizon of truth in which memory and testimony are articulated as modes of salvage’. Orchids: My Intersex Adventure follows a salvaging of the film-maker's life events and experiences, being born with an intersex condition, and, via the filming and editing process, revolving around the core question: who am I? From this transformative creative documentary practice evolves a new way of embodying experience and ‘seeing’, playfully dubbed here as the ‘intersex gaze’.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; australie; autoethnographie; cinéma; cinéma documentaire; communication; corps; cours; discipline; discours dominant; identités; intersexuation; inégalités; océanie; premier cycle; périodes historiques; régions géographiques; sexualité; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales

Lost boys, invisible girls: stories of Sudanese marriages across borders - Grabska, Katarzyna (Gender, Place & Culture, 2010)
Forced migration challenges and changes gender relations. The transnational activities of refugees resettled in the West create gender asymmetries among those who stay behind. This article explores the transnational marriages of young southern Sudanese women (‘invisible girls’), who either stayed in Sudan or remained in refugee camps in Kenya, to Sudanese men who were resettled to America, Canada or Australia (‘lost boys’). Incorporating gender as a relational category into the analysis of transnational practices that migrants and refugees engage in is important. The article argues that there is a need to put feminist analysis at the centre of transnational processes resulting from (forced) migration. It looks at the connections between different geographical locations, the impacts of the migration of young refugee men on bridewealth and marriage negotiations and the gender consequences for young women, men and their families. It is argued that transnational activities, such as marriage, contest, reconfigure and reinforce the culturally inscribed gender norms and practices in and across places. Transnational marriage results in ambiguous benefits for women (and men) in accessing greater freedoms. Anthropological analyses of marriage need a geographical focus on the transnational fields in which they occur. The article seeks to deepen understanding of the nuanced gendered consequences of transnationalism. It shows how gender analysis of actions taken across different locations can contribute to the theorisation of transnational studies of refugees and migrants.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; amériques; anthropologie; anthropologie sociale; approches et analyses; australie; canada; cours; discipline; histoire et politique; kenya; mariage; migration; océanie; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; soudan; systèmes d'oppressions; thématiques; transnationalisme; états-unis

Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences